Discrete choice experiment validation: A resource project case study. (March 2017) - Que, Sisi; Awuah-Offei, Kwame; Weidner, Nathan; Wang, Yumin
Abstract: It is necessary to validate discrete choice experiments to ensure they will lead to reasonable responses and, consequently, to valid modeling results. While some researchers have started to consider the validity of their discrete choice experiments, the approaches used for such validation are not widely reported in the literature. This paper addresses the validation process, which is crucial to the integrity of discrete choice experiments. In particular, this study addresses the selection of attributes and levels, as well as the cognitive load imposed on respondents. This paper presents an approach for discrete choice experimental design and validation for experiments conducted via the Internet. The work covers design, evaluation, and revision to facilitate valid experiments. A focus group study and statistical analysis were used to test the clarity of instructions and difficulty of choices. We show that, in some cases, using respondents' rate of completion, a criterion that is easy to obtain in online surveys, we can confirm self-reported difficulty ratings and improve survey design. Further, we take advantage of other online tools to enhance the clarity of the instructions. These appear to improve clarity and reduce the difficulty of making a choice.